1976
DOI: 10.1159/000208025
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic Aspects of Anemia in Long-Term Hemodialyzed Patients

Abstract: The anemia of dialyzed uremic patients is due to several factors: loss of blood and proteins; increased destruction of erythrocytes, and alteration of erythropoietin feedback. In an anemic dialyzed patient the number of reticulocytes is normal while a sudden worsening of the anemia is followed by severe reticulocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1978
1978
1980
1980

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Similar observations have been reported by Jezuita (1976), who showed that erythrocyte glycolysis is stimulated in haemolytic syndromes with an increase in P" y and also, ADP and ATP, but to a lesser extent in DPG. The shortening of erythrocyte life span has been demonstrated in patients on maintenance dialysis, due mainly to extracorporeal circulation (Buscarini, 1976). The increased carboxyhaemoglobin in our patients may also reflect enhanced haemolysis (Necheles, Rai & Valaes, 1976).…”
Section: Discussionsupporting
confidence: 56%
“…Similar observations have been reported by Jezuita (1976), who showed that erythrocyte glycolysis is stimulated in haemolytic syndromes with an increase in P" y and also, ADP and ATP, but to a lesser extent in DPG. The shortening of erythrocyte life span has been demonstrated in patients on maintenance dialysis, due mainly to extracorporeal circulation (Buscarini, 1976). The increased carboxyhaemoglobin in our patients may also reflect enhanced haemolysis (Necheles, Rai & Valaes, 1976).…”
Section: Discussionsupporting
confidence: 56%
“…A close correlation between glomerulus filtrate and hemoglobin concentration has been noted; in children, r = 0.73 [29]. The two pathoge netic components discussed in renal anemia are an aplastic disorder of the bone marrow, related with an erythropoietine deficiency, and a shortened erythrocyte survival of hitherto unknown reason [1,4,6, 8, 15,[18][19][20][21][22][23][24][38][39][40],In patients with terminal renal insuffi ciency, erythrocyte survival was reduced to 30-60% of the normal value [12, 13]. The hemolytic aspect of anemia in uremia is thought to be caused by alterations in the structure and function of the erythrocytes induced by elevated concentrations of toxic substances in the plasma [21-23, 27, 35, 38-40], The hemolysis-promoting effect of…”
mentioning
confidence: 99%